2008
DOI: 10.3324/haematol.12059
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant erythropoietin found in seized blood bags from sportsmen

Abstract: Recombinant erythropoietin found in seized blood bags from sportsmenDuring an anti-doping investigation, the Spanish Guardia Civil confiscated blood bags from elite sportsmen. A novel immuno-purification method demonstrated that plasma samples with elevated erythropoietin (EPO) contained recombinant material (rEPO). This shows that rEPO is used before autologous blood transfusions and that rEPO analysis in plasma can be reliably addressed. Haematologica 2008 Feb; 93:(2) 313-314. DOI: 10.3324/haematol.12059 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Electrophoresis is especially effective in urine samples, where presence of rhEPO can be identified several days after the last injection. By comparison, detection of rhEPO in serum or plasma, whilst still possible [2] is more challenging due to the lower resolution attainable between the two populations in the more acidic urine matrix [3] as well as the different pI range of endogenous isoforms in blood and urine.…”
Section: Introductionmentioning
confidence: 99%
“…Electrophoresis is especially effective in urine samples, where presence of rhEPO can be identified several days after the last injection. By comparison, detection of rhEPO in serum or plasma, whilst still possible [2] is more challenging due to the lower resolution attainable between the two populations in the more acidic urine matrix [3] as well as the different pI range of endogenous isoforms in blood and urine.…”
Section: Introductionmentioning
confidence: 99%
“…30 Nevertheless, on September 28, 2007, the French sports newspaper L'Equipe reported that the French antidoping laboratory had detected Dynepo (Shire Pharmaceuticals, Hampshire, UK) (epoetin delta) in the urine of Michael Rasmussen during the 2007 Tour de France. As shown by various researchers, 30,73 the IEF profile of epoetin delta, in which more acidic isoforms can be observed with respect to Chinese hamster ovary-derived marketed rhEPOs, 7,74,75 differs from that of endogenous EPO (from either urine or plasma). With the rigorous structural analysis of epoetin delta completed, it can be concluded that when compared with other recombinant EPOs, the more acidic bands present in IEF are the result of a higher degree of sialylation.…”
Section: Criteria For Declaring An Adverse Analytical Findingmentioning
confidence: 93%
“…The three suspicious samples with elevated plasma hEPO concentrations resulted in profiles compatible with the presence of rhEPO. When these samples were immunopurified using the basic and acidic conditions, the profiles obtained were identical, since all bands present are in the basic area for which acidic conditions showed good recoveries [20].…”
Section: Implementation For Human Plasma Samplesmentioning
confidence: 98%